Assessing the effectiveness of Finland’s sustainable development policy to facilitate a sustainability transition - Lyytimäki, Jari; Kentala-Lehtonen, Johanna; Halme, Minna; Linnanen, Lassi; Mönkkönen, Mikko; Ratinen, Ilkka; Salonen, Arto O.; Soini, Katriina; Soininen, Niko; Teperi, Anna-Maria; Toivanen, Reetta (Springer Nature, 2025)
Sustainable development policies have been implemented during several decades, but so far with too little impact apart from awareness raising. Environmental changes, such as biodiversity loss, pollution, and resource overuse, have evolved from local problems to global crises interconnected with social issues like inequality and polarization. The need for rapid and large-scale sustainability transition is evident. Finland is one of the countries with relatively advanced national sustainable development policy and top ranking in several international comparisons of sustainability performance. Focusing on the societal uses of knowledge, this article uses Finland as a case to assess the effectiveness of conventional sustainable development policy, including national strategies, institutions, and practices. Recommendations applicable also for other countries and avenues for more impactful implementation of sustainability solutions are identified, emphasizing the urgent need to adopt a strong sustainability mindset shifting from short-term economic priorities towards coherent long-term targets beyond 2030, with corresponding policy and legal changes.
Keywords: Agenda 2030; Finland; policy effectiveness; sustainable development; sustainability transition